Extração mineral no leito do Rio Curu e as questões socioambientais - Veras, Gustavo Antonio Aniceto (2017)
The Curu Basin is located in the northern region of the State of Ceará and currently the productive areas contribute even more to a dispute and intensification of the conflicts related to the use and demand for water. In the lower course of the basin, there are areas of mineral extraction in the bed of the active channel of the river that affect the river dynamics with the bus and interventions in the river, causing water retention, modification of the hydrodynamic conditions by lowering the fluvial channel and also total decharacterization of the areas of permanent preservation and of the channel bed. It is imperative that the environmental control agencies control and intervene to ensure the correct extraction and minimization of adverse environmental impacts, as well as requiring the implementation of the recovery plan for degraded areas. Organized civil society can also intervene and discuss discussion forums, outlets and solutions to problems affecting the community. In this sense, the Hydrographic Basin Committee (CBH) appears, legally established as the primary administrative body for the resolution and arbitration of conflicts with different social actors, with different views and different actions. CBH - Curu, the first committee installed in Ceará, comes up with a better understanding of the main problems of the Curu Basin in terms of user organization, institutional integration, hydro - agricultural potential and sociocultural dynamics. For conflicts must be faced in their real causes with the effective involvement of all agents and social actors. This paper intends to evaluate if the discussions and debates at the level of the Curu basin committee have been successful in the demands and as preliminary results were identified actions by the control and inspection organs in the application of administrative police power, causing activities that degrade environmental quality. It is necessary to strengthen the control of mining activities and that all the agents involved are responsible for the constant search of the socioenvironmental sustainability of mining activities.